2011
DOI: 10.4161/rna.8.4.16019
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9

Abstract: T he functional significance of microRNA-9 (miR-9) during evolution is evidenced by its conservation at the nucleotide level from flies to humans but not its diverse expression patterns. Recent studies in several model systems reveal that miR-9 can regulate neurogenesis through its actions in neural or non-neural cell lineages. In vertebrates, miR-9 exerts diverse cell-autonomous effects on the proliferation, migration and differentiation of neural progenitor cells by modulating different mRNA targets. In some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 76 publications
(123 reference statements)
6
107
1
1
Order By: Relevance
“…It is exclusively expressed in the sensory neuron and regulates serotonin-mediated synaptic plasticity through the regulation of CREB (Rajasethupathy et al, 2009). In addition to these miRNAs, several miRNAs are reported to be highly enriched in the brain (Sempere et al, 2004), but their roles in synaptic plasticity, learning, and memory are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is exclusively expressed in the sensory neuron and regulates serotonin-mediated synaptic plasticity through the regulation of CREB (Rajasethupathy et al, 2009). In addition to these miRNAs, several miRNAs are reported to be highly enriched in the brain (Sempere et al, 2004), but their roles in synaptic plasticity, learning, and memory are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, forebrain-specific disruption of Dicer1, a key RNase III enzyme for miRNA biogenesis, affected the expression of a set of brain-specific miRNAs and improved performance in learning and memory tasks in adult mice (Konopka et al, 2010). miR-134, which is specifically expressed in the brain, was shown to regulate the size of dendritic spines, excitatory synaptic transmission, and synaptic plasticity (Schratt et al, 2006;Gao et al, 2010). The role of another brain-specific miRNA, miR-124, was studied in the marine snail Aplysia californica (Rajasethupathy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Ma et al reported that miR-9 can increase cell motility and invasiveness through directly targeting CDH1 (the Ecadherin-encoding mRNA), and the expression level of miR-9 is correlated with MYCN amplification, tumor grade, and metastatic status in breast cancer. 19 However, in our studies, miR-9 did not appear to be correlated with lymph node metastasis but instead with histology and stage in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] We have recently started soliciting reviews of notable miRNA families. [19][20][21] One very interesting example from this batch is from Peter Stadler's lab, 22 where an entire undergraduate lab is credited with contributing to the article. This illustrates that this series of articles can be a useful way of training research students and can also bridge views spanning research groups that have not traditionally collaborated.…”
mentioning
confidence: 99%